PENERAPAN STRATEGI SELF REGULATED LEARNING PADA PEMBELAJARAN DARING - Bernadus Nifmaskossu; Yowelna Tarumasely; Febby Pelupessy (TANGKOLEH PUTAI, 2022)
This study aims to find out how the implementation of the self-regulated learning strategy by class VIII.3 students of SMP Negeri 6 Ambon in PAK learning in online learning. The method used in this study is a qualitative method, the informants used in this study were 19 people. Data collection techniques using interviews. The results showed: self-regulated learning strategies, namely self-evaluation, organizing and changing, setting goals and planning, seeking information, noting important things, managing the environment, self-consequences, repeating and remembering, and seeking social support, have been applied by class students. VIII.3 but not maximal.